2010
DOI: 10.21061/jcte.v25i2.481
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship Between SkillsUSA Student Contest Preparation and Academics

Abstract: Career and Technical Student Organizations (CTSOs) assert they are assisting students in developing leadership, teamwork, citizenship, problem solving, communication, and academic skills for workplace success, but with limited research on their outcomes, are these empty claims? With integration of academics being a major Career and Technical Education (CTE) priority, and CTSOs named integral partners in meeting requirements of the 2006 Perkins legislation, this study has been conducted for the purpose of (a) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This method has been shown to increase effectiveness in a number of studies (e.g. Beersma et al, 2003;Threeton & Pellock, 2010). Beyond the classroom, student competition can be elevated to college, national, and international levels that increase the perceived benefits, such as potential recognition for winners.…”
Section: "Competition and Competitive Rhetoric Can Be Healthy It's Wmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been shown to increase effectiveness in a number of studies (e.g. Beersma et al, 2003;Threeton & Pellock, 2010). Beyond the classroom, student competition can be elevated to college, national, and international levels that increase the perceived benefits, such as potential recognition for winners.…”
Section: "Competition and Competitive Rhetoric Can Be Healthy It's Wmentioning
confidence: 99%
“…He observed that the contest actually increases student motivation and learning outcomes, and students prefer the contest over the conventional lab. Regarding the particular learning outcomes of using contests, Threeton and Pellock (2010) find that participation in the SkillsUSA Occupational Health and Safety national competition fulfills three out of four competency categories in reading standards. In state FFA contests, Johnson (1993) finds that the learning results are positively related to the achievement in the student contest.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Career and Technical Student Organizations (CTSOs) are a major component of Career and Technical Education (CTE) (Threeton & Pellock, 2010). Aligned with school-based agricultural education (SBAE), the National FFA Organization is one of eight nationally recognized CTSOs.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of this approach in the OR curriculum is that industry engagement is with a single client, and a competition is set up among student teams. Student team competitions have shown to be effective in promoting academic performance (e.g., Beersma et al 2003, Threeton andPellock 2010), and developing interpersonal and intrapersonal attributes (Tauer and Harackiewicz 2004). Academic contests have successfully been integrated into the business course curriculum through semester-long, competitive, team projects (e.g., Özpolat et al 2014), yet not in the OR curriculum.…”
Section: Introductionmentioning
confidence: 99%